Development of an on-line interactive map to display environmental health assessments of Canadian communities: knowledge-translation to support collaborations for health. Issue 2 (30th November 2018) - de Souza, R. J.; Arora, R.; Gauvin, L.; Williams, N. C.; Lear, S. A.; Oliveira, A. P.; Desai, D.; Corsi, D. J.; Subramanian, S. V.; Rana, A.; Booth, G. L.; Razak, F.; et al.
ABSTRACT: Contextual determinants of health in Canada include community demographics, tobacco, food, and alcohol. We developed an on-line and highly accessible interactive map containing information from over 2000 communities across Canada.